2020
DOI: 10.1097/sap.0000000000002304
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lid Crease Measurements in Levator Advancement for Ptosis

Abstract: Purpose Although previous reports addressed the differences in marginal reflex distance 1 (MRD-1) measurements based on various techniques of levator advancement, eyelid crease measurements have not been studied as markers in perioperative planning. In addition to possible benefits in optimal results for improvement of visual field defects and functional impairment, recent work has suggested that eyelid crease is important in the perception of attractiveness. Therefore, the aims of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Makeeva et al 16 have found that a 4-mm advancement resulted in an average MRD1 increase of 2.26 mm and a 5-mm advancement increased to 2.74. Alkeswani et al 17 have found that a 4-mm average advancement led to an average of 2.2 mm increase in MRD1, whereas a 5mm advancement led to an average increase of 2.9 mm. Although these studies suggested a consistent relationship between the levator advancement distance and improvement in MRD1 measurement can be used to plan the amount of advancement required to elevate the eyelid.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Makeeva et al 16 have found that a 4-mm advancement resulted in an average MRD1 increase of 2.26 mm and a 5-mm advancement increased to 2.74. Alkeswani et al 17 have found that a 4-mm average advancement led to an average of 2.2 mm increase in MRD1, whereas a 5mm advancement led to an average increase of 2.9 mm. Although these studies suggested a consistent relationship between the levator advancement distance and improvement in MRD1 measurement can be used to plan the amount of advancement required to elevate the eyelid.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To the Editor: W e thank the authors for sharing their useful experience in microsurgical reconstruction of lower leg defects using the medial sural artery and vein(s) as recipient vessels. 1 This possibility has been widely explored in literature in the setting of posttraumatic conditions; however, only a few articles addressed it in postoncological reconstruction. Vessels depletion, indeed, is a common issue in lower leg traumatic injuries, but is less frequent in oncological surgery.…”
Section: Reconstruction Of the Posterior Compartment Of The Leg With ...mentioning
confidence: 99%
“…We read with great interest the article titled “Changes in lid crease measurements in levator advancement for ptosis” by Alkeswani et al, 1 in which authors reported the change in eyelid crease measurements in levator advancement, also explaining preoperative planning to avoid overcorretion or undercorretion during ptosis surgery.…”
mentioning
confidence: 99%